PROGRESSIVE CHELAR POLYMORPHISM IN THE MANGROVE CRAB, UCIDES CORDATUS (LINNAEUS, 1763) (DECAPODA, BRACHYURA, OCYPODIDAE) FROM THE SOUTH-WESTERN ATLANTIC - João, Marcio C.A. [UNESP]; Kriegler, Nicholas [UNESP]; Hernáez, Patricio; Pinheiro, Marcelo A.A. [UNESP] (Brill Academic Publishers, 2024)
Morphological variation of body size and appendages is defined as polymorphism and may be associated with important structures linked to the sexual selection process. Some studies have suggested an expressive heterochely (i.e., dissimilar chelipeds) in the male adult phase of the semiterrestrial crab Ucides cordatus, an important decapod species of mangrove systems from the western Atlantic. Here, the morphology, size, and growth pattern of male chelipeds in U. cordatus from the Brazilian coast were examined to test for polymorphism, considering that adult males usually develop one ornamented and hypertrophied cheliped. Two cheliped morphs were detected in U. cordatus males: chelipeds can be either homochelous or heterochelous and both morphotypes occur from the juvenile to adult phase. The higher frequencies of heterochelous males in larger size classes (71%: >51 mm CW) and homochelous males in smaller ones (56%: <51 mm CW) confirmed that the prevalence of each morph is also associated with the ontogeny in males. The ornamentation of both morphs mainly differed in the dentition of cutting edges, but it was similar in the presence and position of tubercles. Adult crabs with homochelous and heterochelous chelipeds reached a similar body size, but their major chelipeds were significantly different in size and growth pattern. The presence of both cheliped morphs suggests the existence of distinct functions in this species, associated with feeding habits and behavioral displays (sexual / agonistic interactions). Our results indicate that more than one morph can participate in the reproductive process in species with mating systems (e.g., explosive breeding) allowing for this, as in the subfamily Ucidinae.
Keywords: Chela; chelar functionality; mating system; polymorphism; reproduction